On a boundary value problem for nonlinear functional differential equations. (13th November 2005) - Hakl, Robert
Abstract : We consider the problemu ′ ( t ) = H ( u ) ( t ) + Q ( u ) ( t ), u ( a ) = h ( u ), whereH, Q : C ( [ a, b ] ; R ) → L ( [ a, b ] ; R ) are, in general, nonlinear continuous operators, H ∈ ℋ a b α β ( g 0, g 1, p 0, p 1 ), andh : C ( [ a, b ] ; R ) → R is a continuous functional. Efficient conditions sufficient for the solvability and unique solvability of the problem considered are established.